Peran Kepemilikan Institusional Sebagai Variabel Pemoderasi Analisis Pengaruh Rasio Kecukupan Modal Dan Green Banking Terhadap Pertumbuhan Profitabilitas Perusahaan Perbankan Yang Terdaftar Di Bei Periode 2021-2024 - Septiola Hutagalung Lamria; Lamria Sagala; Wesly A. Simanjuntak (Politeknik Raflesia Press, 2026)
This study aims to analyze and assess the effect of Capital Adequacy Ratio and Green Banking on profitability growth with institutional ownership as a moderating variable in banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. The research sample included 32 companies that met the criteria through purposive sampling. The analysis method used was multiple linear regression analysis using SPSS version 26 software. The results showed that the Capital Adequacy Ratio had a positive and significant effect on profitability growth, and Green Banking had a positive and statistically significant effect on profitability growth. Simultaneously, both variables had a significant effect on profitability growth. The coefficient of determination (R) test results show that the Capital Adequacy Ratio and Green Banking can explain 26% of the variation in Profitability, while the remaining 74% is explained by other factors not included in the model. In testing the moderating effect, it was found that the institutional ownership variable was unable to moderate the relationship between the Capital Adequacy Ratio and profitability growth, but it could moderate the relationship between Green Banking and profitability growth. The researchers suggest that future researchers increase the number of years of observation so that the research results are better and the impact of the research variables can be clearly seen.